2004
DOI: 10.1002/aheh.200300526
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Iron on Surfaces: Modelling, Data Evaluation, and Measurement Uncertainty

Abstract: Assessment of the likely outcome of engineered invention strategies in acid mine drainage often involves complex geochemical modelling activities. Geochemical modelling is based on chemical thermodynamic data. In addition sorption models, kinetical reaction rates and transport tools are included into the modelling codes because the interactions between solution components and surfaces, reaction time and transport are considered important features characterising the site‐specific situation. In the determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The boomerang-shaped field represents the pH-E H region of natural waters as determined by Baas-Becking et al (1960). The data follow the lower boundary set for oxidized mine water and correlate closely with the E H -pH calculated for the Fe(III)/Fe(II) couple (Meinrath et al, 2004). The redox regime is strongly influenced by the shallow layer of tailings, affected by AMD.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The boomerang-shaped field represents the pH-E H region of natural waters as determined by Baas-Becking et al (1960). The data follow the lower boundary set for oxidized mine water and correlate closely with the E H -pH calculated for the Fe(III)/Fe(II) couple (Meinrath et al, 2004). The redox regime is strongly influenced by the shallow layer of tailings, affected by AMD.…”
Section: Resultssupporting
confidence: 71%
“…The question, whether a Fe(II) sulfate phase should be solubility limiting will not be further discussed. The authors are well aware of the limitations of thermodynamic modelling (Meinrath et al, 2000, Meinrath 2001, Meinrath & May, 2002, Meinrath et al, 2004, Ödegaard-Jensen et al, 2004. In Figure 3 the concentrations of Fe and S in the WA sample from the l996 sampling campaign are correlated with concentrations which remain after 10 days in solution, after filtration through 0.45 µm filter paper (FAS).…”
Section: Resultsmentioning
confidence: 99%
“…Nitzsche et al (2000) or Meinrath et al (2004) varied different constants in the database within their error range and were able to show the uncertainties of such numerical codes -and their results might be surprising for those who tend to discuss the 2 nd or 3 rd decimal place in the results of the programmes (Fig. Yet, the chemical thermodynamic database is based on experimental results, which have an inherent experimental error range.…”
Section: Geochemical Modellingmentioning
confidence: 99%
“…Water Environment Research, Volume 77, Number 6 1882 found to have the highest bioavailability and highest probability of being remobilized under changing water quality conditions. In an effort to better understand the reliability of complex geochemical modeling exercises, Meinrath et al (2004) used a probabilistic speciation code (Ljungskile) to identify the complete measurement uncertainty budget.…”
Section: Environmental Fate and Transportmentioning
confidence: 99%